(untitled) (Italian Journal of Public Health, 2011)
The quality of scientific evidence is doubly tied with the quality of all research activities that generates it (including the “value” of the scientists involved) and is usually, but not always, reflected in the reporting quality of the scientific publication(s). Public health practitioners, either at research, academic or management levels, should be aware of the current metrics used to assess the quality value of journals, single publications, research projects, research scientists or entire research groups. However, this task is complicated by a vast variety of different metrics and assessment methods. Here we briefly review the most widely used metrics, highlighting the pros and cons of each of them. The rigid application of quantitative metrics to judge the quality of a journal, of a single publication or of a researcher suffers from many negative issues and is prone to many reasonable criticisms. A reasonable way forward could probably be the use of qualitative assessment founded on the indications coming from few but robust quantitative metrics.